2019
DOI: 10.1364/boe.10.000600
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the application of Raman spectroscopy together with chemometric technique for screening of asthma disease

Abstract: Medical biophotonic tools provide new sources of diagnostic information regarding the state of human health that are used in managing patient care. In our current study, Raman spectroscopy, together with the chemometric technique, has successfully been demonstrated for the screening of asthma disease. Raman spectra of sera samples from asthmatic patients as well as healthy (control) volunteers have been recorded at 532 nm excitation. In healthy sera, three highly reproducible Raman peaks assigned to β-carotene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…The decrease in β-carotene in the diseased serum samples is consistent with previous research [29] . In addition, some weak difference Raman peaks appear at 962, 1127, 1297, 1335, 1447, 1584, and 1653cm −1 can also be found.…”
Section: Raman Spectra Of Serum Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease in β-carotene in the diseased serum samples is consistent with previous research [29] . In addition, some weak difference Raman peaks appear at 962, 1127, 1297, 1335, 1447, 1584, and 1653cm −1 can also be found.…”
Section: Raman Spectra Of Serum Samplessupporting
confidence: 92%
“…4 and porphyrin content variation [28] . Two high intensity Raman peaks at 1156 and 1519 cm −1 due to the resonance raman effect belonging to β-carotene are strongly enhanced under excitation at 532 nm [28,29] .…”
Section: Raman Spectra Of Serum Samplesmentioning
confidence: 99%
“…The peak assignments are listed in Table 3 according to the reported literature. [11,14,[21][22][23][24][25][26][27][28] The HGG and LGG group peak intensity changes compared with the normal group are shown in Table 2. The HGG group had lower intensities than the LGG group at all specific peaks except 749 cm −1 .…”
Section: Spectral Analysismentioning
confidence: 99%
“…T A B L E 3 Raman peak attribution in normal and glioma serum [11,14,[21][22][23][24][25][26][27][28] Raman shift (cm − PCA-LDA for glioma diagnosis, an ROC curve was produced, as shown in Figure 3b, and the accuracy of the discriminant analysis results was evaluated by the area under the ROC curve. Therefore, we performed a pairwise comparison of the PCA-LDA diagnostic algorithm results.…”
Section: Principal Component Analysis (Pca) and Linear Discriminantmentioning
confidence: 99%
“…6 Ullah et al reported the ability of Raman technique for asthma screening by demonstrating the effective classication of serum spectra from asthmatic and healthy individuals using PLS-DA. 7 Raman spectroscopy analysis have been reported as a potential tool in order to evaluate the therapeutic response in patients suffering from breast cancer. The relative changes of biomolecules such as tryptophan, tyrosine, phenylalanine, proteins, carotenoids and lipids in blood plasma have been observed in the Raman spectrum which was good enough to discriminate pre and post treatment conditions.…”
Section: Introductionmentioning
confidence: 99%